Quality of Work Life at Airport Management Unit (UPBU) Merauke - Elly Noer; Jacobus Rico Kuntag (AIBPM Publisher, 2024)
The aim of this study is to investigate the indicators of work life quality among employees at the Airport Management Unit (UPBU) Class 1 Mopah Merauke. A qualitative approach was adopted by collecting data from semi-structured in-depth interviews with 12 civil servants representing the administration sub-section, the technical operations section, the flight security section, as well as the service and cooperation section. The research findings indicate that the first determinant of work life quality is the opportunity to use and develop expertise. Skill development is an essential factor to ensure the safety and efficiency of employee work. Without the proper skills, operations could be hindered. The second indicator is the condition of a safe and comfortable work environment. Safety and health are the top priorities at the airport. The third indicator is constitutionalism within the work organization. Legal protection and employees' rights are crucial, especially in a highly structured and high-risk environment like the airport. The other four indicators, although not primary, can influence employee job satisfaction at the airport, especially if the other factors are already satisfied. The results of this study provide valuable insights into the challenges faced by employees at UPBU and offer recommendations for further improvement.